Gender analysis on sustainable consumption behaviour among homestay guest at Langkawi Island - Jamaluddin, Askiah; Zulkifle, Zuzafina; Zainalaluddin, Zumilah (Human Resource Management Academic Research Society, 2022)
The purpose of this study is to study gender analysis on sustainable consumption behaviour among homestay guests at Langkawi Island. Homestay guests who practice sustainable consumption behaviour, which begins with planning, consumption and disposal, will enhance a better environment. Sustainable consumption behaviour is the root of sustainable development. Sustainable development could not succeed without the person who is managing and implementing the planning, consumption and disposal of the limited resources they have. In this study, there are 364 homestay gguestsas a respondent. Based on that total number of the respondent, 70% are male and 30% are female. Mostly, the homestay guest is from B40 groups whose household income per month is less than MYR4000. The majority of the homestay guest is the young male age less than the 30s, while the female is older than male. Based on the analysis, the female is more on planning and consumption aspects, while the male is more on disposal aspects. The analysis is relevant to past research, where female likely practices sustainable consumption compared to male. This finding contributes to a new body of knowledge about the behaviour of homestay guests in Langkawi Island related to sustainable consumption activities. The data is important to LADA, MOTAC, homestay owners, local residents, and academicians on how to develop a culture of sustainable consumption behaviour, encourage the domestic traveller to visit Langkawi as well as care the Langkawi’s sustainability.